Jernej Kopitar - novi pogledi na njegovo osebnost in delovanje - Hafner, Stanislaus (Slavistična revija, 1998)
In a relatively short period of time Jernej Kopitar was able to become oriented and to gain recognition as a linguist and Slavist in the first universal phase of Viennese Romanticism. The pecularities of the language of his correspondence, which depend on the addressee, indicate Kopitar's formed perosnality and serve as characterization of his cultural-political views, as the author attempt to explain them.
Keywords: Kopitar, Jernej; slovenski jezikoslovci; slovenščina